2017
DOI: 10.1590/1980-5373-mr-2016-0870
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Morphological and Mechanical Characterization of Recycled Poly (Ethylene Terephthalate) Blends and Composites

Abstract: This study evaluated the effect of adding poly (ethylene methyl acrylate) (EMA) and cotton linter (CL) on the properties of recycled poly (ethylene terephthalate) (PET rec ). For this, PET rec /EMA blend and PET rec /EMA/CL composite were developed. In order to improve the interfacial adhesion and the properties of these materials, ethylene/methyl acrylate/glycidyl methacrylate terpolymer (EMA-GMA) and polyethylene-grafted maleic anhydride (PE-g-MAH) were added. The rheological results showed that the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…In particular, the modulus increased from 777 MPa (neat bio-PET piece) up to 1124 MPa (bio-PET/RCF composite piece with 10 wt% RCF). Similar results were found in the literature for other composite systems based on NFs in absence of compatibilizers [28,47,57,58,59]. The addition of RCF also provided an increase in the Shore D hardness values.…”
Section: Resultssupporting
confidence: 89%
“…In particular, the modulus increased from 777 MPa (neat bio-PET piece) up to 1124 MPa (bio-PET/RCF composite piece with 10 wt% RCF). Similar results were found in the literature for other composite systems based on NFs in absence of compatibilizers [28,47,57,58,59]. The addition of RCF also provided an increase in the Shore D hardness values.…”
Section: Resultssupporting
confidence: 89%
“…Possible reactions between the carboxyl and hydroxyl groups of PET and the epoxy groups present in EGMA and EMAGMA copolymers : (a) Esterification. (b) Etherification.…”
Section: Resultsmentioning
confidence: 99%
“…Pereira et al , studying the effect of EMAGMA copolymer on PET/EMA blend reported that the reactions between the carboxyl or hydroxyl groups of PET with the epoxy groups led to the increase in the molar mass. The authors further confirmed, by MFI analysis, that the MFI of PET/EMA blend decreased with the addition of EMAGMA copolymer due to the chemical reactions between PET functional groups and the epoxy groups of EMAGMA.…”
Section: Resultsmentioning
confidence: 99%
“…Na literatura observa-se que estudos relacionados à reatividade de copolímeros com poliésteres, como o PET, que apresentam grupos terminais hidroxila (-OH) e carboxila (-COOH) em sua estrutura química, foram realizados visando modificar as propriedades de fluxo, quando em processamento e também as propriedades mecânicas (módulo) e tenacidade, após a moldagem por processos convencionais como extrusão e injeção [6][7][8]. Alguns autores identificaram que os copolímeros contendo grupos funcionais metacrilato de glicidila (-GMA) em sua composição química, reagem com poliésteres durante o processamento, atuando como agentes de extensão e/ ou ramificação da cadeia aumentando a viscosidade do fundido e consequentemente melhorando as propriedades mecânicas, principalmente resistência ao impacto, sem perder de forma significativa a rigidez [9].…”
Section: /8unclassified